Assessment of Oxidative Stress Markers in Hypertensive Patients under the Use of Renin-Angiotensin-Aldosterone Blockers - Nestor Vazquez-Agra; Ana-Teresa M; Anton Cruces-Sande; Estefania Mendez-Alvarez; Ramon Soto-Otero; Jose-Enrique; Antonio Pose-Reino; Alvaro Hermida-Ameijeiras (MDPI AG, 2023)
As in other fields, chronotherapy applied to arterial hypertension (AHT) may have implications on oxidative stress. We compared the levels of some redox markers between hypertensive patients with morning and bedtime use of renin-angiotensin-aldosterone system (RAAS) blockers. This was an observational study that included patients older than 18 years with a diagnosis of essential AHT. Blood pressure (BP) figures were measured using twenty-four-hour ambulatory BP monitoring (24-h ABPM). Lipid peroxidation and protein oxidation were assessed using the thiobarbituric acid reactive substances (TBARS) and reduced thiols assays. We recruited 70 patients with a median age of 54 years, of whom 38 (54%) were women. In hypertensive patients with bedtime use of RAAS blockers, reduced thiol levels showed a positive correlation with nocturnal diastolic BP decrease. TBARS levels were associated with bedtime use of RAAS blockers in dipper and non-dipper hypertensive patients. In non-dipper patients, bedtime use of RAAS blockers was also associated with a decrease in nocturnal diastolic BP. Chronotherapy applied to bedtime use of some BP-lowering drugs in hypertensive patients may be linked to a better redox profile.